A extensão universitária e o Sistema de Informação da Extensão (SIEX/UFMG): um estudo de usuários a partir de uma perspectiva compreensiva - Ana Luisa de Vasconcelos Terto (2013)
This research is about a study of the users Information System Extension, Federal University of Minas Gerais ( SIEX/UFMG ). The major objective of this study is to investigate the information practices of the users in the mentioned system, covering the behavioral aspects of their users and the operational aspects of the system. The motivation for this work grew up by the volume of shares registered in SIEX/UFMG since its launch and the author's experience in mediating the interaction between the user - system. Believed, this research will contribute to the extension activities UFMG to give a voice to users SIEX/UFMG and find out their perceptions of the system and the extension, allowing the implementation of improvements in accordance with the notes of the participants as to research in information science, particularly in the area of the user studies, to perform work in accordance with the proposed expansion of its planning research, seeking the analysis of human action and the study of the user behavior. The theoretical contribution sought adopted in the literature on (i) user studies - approaching this research studies the social approach - ,(ii) social phenomenology - so you can , in line with the studies of the users approach social , seeking to understand informational practices of users SIEX/UFMG and (iii) usability criteria - to verify user perception in relation to the system used. To understand the motivations and perceptions of the users, we used in-depth semi-structured interviews to collect data, which generated a large amount of comprehensive and descriptive results, bringing relevant considerations about SIEX/UFMG and extension activities at UFMG.